2021
DOI: 10.1038/s41598-021-90067-z
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: The effect of taxonomic classification by full-length 16S rRNA sequencing with a synthetic long-read technology

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Amplicon-based sequencing of marker genes [16S rDNA, 18S rDNA, or ITS regions] have always been plagued by insufficient taxonomic resolutions due to inability of the present sequencing to sequence the whole gene. New long-read sequencing technologies like PacBio circular consensus sequencing and loop genomics synthetic long-read sequencing technology [sFL16S] can sequence the entire marker gene such as 16S rRNA gene [ 14 , 65 ]. These techniques could overcome the microbial misidentification caused by previous approach’s inability to sequence the whole marker gene and could correctly classified to the sub-species clades [ 14 , 65 ].…”
Section: Challenges and Prospects In Unboxing The Black Box Of Soil M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Amplicon-based sequencing of marker genes [16S rDNA, 18S rDNA, or ITS regions] have always been plagued by insufficient taxonomic resolutions due to inability of the present sequencing to sequence the whole gene. New long-read sequencing technologies like PacBio circular consensus sequencing and loop genomics synthetic long-read sequencing technology [sFL16S] can sequence the entire marker gene such as 16S rRNA gene [ 14 , 65 ]. These techniques could overcome the microbial misidentification caused by previous approach’s inability to sequence the whole marker gene and could correctly classified to the sub-species clades [ 14 , 65 ].…”
Section: Challenges and Prospects In Unboxing The Black Box Of Soil M...mentioning
confidence: 99%
“…New long-read sequencing technologies like PacBio circular consensus sequencing and loop genomics synthetic long-read sequencing technology [sFL16S] can sequence the entire marker gene such as 16S rRNA gene [ 14 , 65 ]. These techniques could overcome the microbial misidentification caused by previous approach’s inability to sequence the whole marker gene and could correctly classified to the sub-species clades [ 14 , 65 ]. These techniques could in turn generate high quality sequences from the unculturable environmental organisms, which can then help in developing robust databases including such environmental sequences.…”
Section: Challenges and Prospects In Unboxing The Black Box Of Soil M...mentioning
confidence: 99%
“…A previous study also reported that the Rubellimicrobium genus completely disappeared once plants grew on the soil (Köberl et al, 2013), despite Kocuria species being known to tolerate salinity, promote plant growth, and increase their ability to resist disease (Goswami et al, 2014). Recent studies recommended accurate species classification in other regions such as V2-V3 (Bukin et al, 2019) or other newer methods such as sFL16S (Jeong et al, 2021). However, some of the observed unidentified species could be due to the novelty of the species, as many belonged to relatively new genera and families.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing interest and development of protocols for full-length 16S rRNA gene sequencing (Callahan et al, 2019 ; Jeong et al, 2021 ; Matsuo et al, 2021 ) and metagenomic methods (Milanese et al, 2019 ; Ye et al, 2019 ; Lu and Salzberg, 2020 ), short-read amplicon analysis remains popular for studying microbial communities due to the comparative low-sequencing costs and high accuracy. Drawbacks of the short-read approach are the lower phylogenetic signal provided by short reads and the amplification efficiency bias that primer pairs can exhibit toward certain taxa (Albertsen et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%